Perancangan dan Implementasi Produk UMKM Aplikasi Vegetarian “VegeYuk” Berbasis Android - Robi Robi; Yonky Pernando (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the global economy. In today's digital era, Android technology has become a highly useful tool for promoting products and providing services to users. This research aims to develop an Android application called